Enabling people with intellectual and other disabilities to make verbal requests using cardboard chips with mini objects or pictures and a smartphone - Lancioni, Giulio E.; Singh, Nirbhay N.; O’Reilly, Mark F.; Sigafoos, Jeff; Alberti, Gloria; Troccoli, Oriana; Orlando, Isabella; Ricci, Carlo (Frontiers in Rehabilitation Sciences, 2023)
Objective: This study aimed to help six participants with intellectual disability combined with sensory and motor impairments to make verbal requests through the use of a technology system involving cardboard chips and a smartphone.The participants were divided into two groups of three based on whether they did or did not have visual skills. Each group was exposed to the intervention with the technology system according to a non-concurrent multiple baseline across participants design. During the 20-min intervention sessions, the participants were provided with a smartphone and nine cardboard chips each of which had a picture or object (i.e., a mini object replica or raised object contour) and several radio frequency identification tags attached to it. To make a request, the participants were to bring a cardboard chip in contact with the smartphone. This read the tags attached to the cardboard and verbalized the request related to that cardboard.Results: During the baseline (without cardboard chips and smartphone), the participants' mean frequency of independent requests (all non-verbal requests) varied between zero and near 1.5 per session. During the intervention (with cardboard chips and smartphone), the participants' mean frequency of independent requests (all verbal requests) varied between over 4.5 and about 10 per session.The results suggest that the system might be useful to help participants like the ones included in this study to make verbal requests with simple responses.